Directional Reconstruction of Iron Oxides to Active Sites for Superior Water Oxidation - Liu, Hai‐Jun; Zhang, Shuo; Yang, Wen‐Yu; Yu, Ning; Liu, Chun‐Ying; Chai, Yong‐Ming; Dong, Bin (Advanced functional materials, 2023)
Rationally constructing and manipulating the in situ formed catalytically active surface of catalysts remains a tremendous challenge for a highly efficient water electrolysis. Herein, an anion and cation co‐induced strategy is presented to modulate in situ catalyst dissolution‐redeposition and to achieve the directional reconstruction of Zn and S co‐doped Fe 2 O 3 and Fe 3 O 4 on iron foams (Zn,S‐Fe 2 O 3 ‐Fe 3 O 4 /IF), for oxygen evolution reaction (OER). Benefiting from Zn, S co‐doping and the presence of Fe 3 O 4 , a directionally reconstructed surface is obtained. The Fe 2 O 3 in the Zn,S‐Fe 2 O 3 ‐Fe 3 O 4 /IF is directionally reconstructed into FeOOH (Zn,S‐Fe 3 O 4 ‐FeOOH/IF), in which the S leaching promotes the Fe dissolution and the Zn co‐deposition regulates the activity of the obtained FeOOH. Moreover, the presence of Fe 3 O 4 provides a stable site for FeOOH deposition, and thus causes more FeOOH active components to be formed. Directionally reconstructed Zn,S‐Fe 3 O 4 ‐FeOOH/IF outperformes many state‐of‐the‐art OER catalysts and demonstrates a remarkable stability. The experimental and density functional theory (DFT) calculation results show that the introduction of Zn‐doped FeOOH with abundant oxygen vacancies through directional reconstruction has activated lattice O atoms, facilitating the OER process on the heterojunction surface following the lattice oxygen mechanism (LOM) pathway. This work makes a stride in co‐induced strategy modulating directional reconstruction.